Hubungan Antara Pengetahuan dan Gaya Hidup dengan Hipertensi di Puskesmas Depok 2 Condong Catur Depok Sleman - Eltanina Ulfameytalia Dewi; Maria H. Bakri; Yohanes Dari (LPPM STIKES Guna Bangsa, 2017)
Background: Hypertension is non-contagious disease caused by several factors such as stress, obesity, nutritions, and life style. Some people were known to consume junk food, smoking, and never routinely exercise. Objective: The aim is to find out the relationship of knowledge and life style with hypertension at Puskesmas Depok 2 Condong Catur Sleman Yogyakarta. Method: This is an analytical correlation research with cross sectional method. This research was conducted outpatient who attended Puskesmas Depok 2 Condong Catur Sleman Yogyakarta using purposive sampling as many with 129 patients. Result: Knowledge as general is enough 48,1% and life syle(41,1%). Hypertension as moderate level 49,6%. Ther is correlation between knowledge and life style with hypertention p value 0,000. Conclusion: There is a significant correlation between knowledge and life style with hypertension.